The Art and Technique of Digital Color Correction. - Hullfish, Steve (Elsevier Science, 2012)
The only guide to the art and technique of color correction based on the invaluable knowledge of more than a dozen of the top colorists in the world. This book allows you unprecedented access to the way the masters of the craft approach their work. Containing decades of industry experience and professional colorist know-how, this book provides an understanding of what top-tier colorists look for in an image and how they know what to do to make it great. Featuring techniques performed in a variety of color correction software applications (DaVinci Resolve, Apple Color, Synthetic Aperture's Col.